Dopamine response gene pathways in dorsal striatum MSNs from a gene expression viewpoint: cAMP-mediated gene networks - Vladimir N. Babenko; Anna G. Galyamina; Igor B. Rogozin; Dmitry A. Smagin; Natalia N. Kudryavtseva (BMC Neuroscience, 2020)
Abstract Background Medium spiny neurons (MSNs) comprise the main body (95% in mouse) of the dorsal striatum neurons and represent dopaminoceptive GABAergic neurons. The cAMP (cyclic Adenosine MonoPhosphate)—mediated cascade of excitation and inhibition responses observed in MSN intracellular signal transduction is crucial for neuroscience research due to its involvement in the motor and behavioral functions. In particular, all types of addictions are related to MSNs. Shedding the light on the mechanics of the above-mentioned cascade is of primary importance for this research domain. Results A mouse model of chronic social conflicts in daily agonistic interactions was used to analyze dorsal striatum neurons genes implicated in cAMP-mediated phosphorylation activation pathways specific for MSNs. Based on expression correlation analysis, we succeeded in dissecting Drd1- and Drd2-dopaminoceptive neurons (D1 and D2, correspondingly) gene pathways. We also found that D1 neurons genes clustering are split into two oppositely correlated states, passive and active ones, the latter apparently corresponding to D1 firing stage upon protein kinase A (PKA) activation. We observed that under defeat stress in chronic social conflicts the loser mice manifest overall depression of dopamine-mediated MSNs activity resulting in previously reported reduced motor activity, while the aggressive mice with positive fighting experience (aggressive mice) feature an increase in both D1-active phase and D2 MSNs genes expression leading to hyperactive behavior pattern corresponded by us before. Based on the alternative transcript isoforms expression analysis, it was assumed that many genes (Drd1, Adora1, Pde10, Ppp1r1b, Gnal), specifically those in D1 neurons, apparently remain transcriptionally repressed via the reversible mechanism of promoter CpG island silencing, resulting in alternative promoter usage following profound reduction in their expression rate. Conclusion Based on the animal stress model dorsal striatum pooled tissue RNA-Seq data restricted to cAMP related genes subset we elucidated MSNs steady states exhaustive projection for the first time. We correspond the existence of D1 active state not explicitly outlined before, and connected with dynamic dopamine neurotransmission cycles. Consequently, we were also able to indicate an oscillated postsynaptic dopamine vs glutamate action pattern in the course of the neurotransmission cycles.